FEMALE DIRECTORS, FOREIGN DIRECTORS, FIRM PERFORMANCE, AND CREDIT RISK: EVIDENCE FROM ASEAN BANKING FIRMS 2020-2024 - Olivia Ovania; Sarwenda Biduri (Antis Publisher, 2025)
Objective: This study aims to analyze the influence of female directors, foreign directors, board size, bank size, net interest margin (NIM), and loan-to-asset ratio (LTA) on financial performance (ROA) and credit risk (NPL) in banks across five ASEAN countries. Method: Using panel data from 2020–2024 (N=35, T=5; 175 observations), the research employs panel regression with Chow, Hausman, and LM tests to determine the most appropriate estimation model, resulting in the application of the Random Effects Model (REM) using GLS. Results: The findings reveal that female directors significantly decrease financial performance, while foreign directors significantly enhance it, although neither influences credit risk. The control variables show mixed effects: larger boards and banks reduce performance and increase credit risk, NIM increases performance but simultaneously elevates risk, and LTA significantly raises credit risk. Novelty: This study offers new empirical insights by simultaneously examining board diversity, governance structure, and financial indicators in a cross-country ASEAN banking context during the post-pandemic period, highlighting the governance–risk–performance trade-off often overlooked in previous studies.